MON-374 Management of 1,25-dihydroxyvitamin D (1,25-OHD) Mediated Hypercalcemia of Unknown Etiology - Menon, Sruthi (J Endocr Soc, 2020)
Background: We describe the diagnostic dilemma and treatment challenges faced in a rare case of 1,25-OHD mediated hypercalcemia. Clinical Case: A 13 year old boy was admitted with severe hypercalcemia (calcium 15.5 mg/dl) in the setting of a non-specific rash, malaise, pancytopenia and acute kidney injury. He was incidentally also noted to have hypogammaglobulinemia a few months prior to presentation. Blood tests were suggestive of hypercalcemia mediated by 1,25-OHD (level >200 pg/ml; ref: 30-83 pg/ml). 25-hydroxy vitamin D was normal (29 ng/ml) and PTH was appropriately suppressed (<4 pg/ml). Workup for various etiologies including infectious, rheumatologic and oncologic diseases associated with ectopic production of 1,25-OHD was initiated. Hypercalcemia was initially managed with hyperhydration, furosemide and calcitonin. However after a brief period of improvement in hypercalcemia, levels started to rise again despite increasing calcitonin dose and frequency (secondary to tachyphylaxis). Kidney function also started to worsen. Extrarenal 1-alpha hydroxylase activity can be suppressed using steroid therapy, however it was contraindicated at the time given that malignancy and other infectious etiologies had not been excluded. At that point, a trial of zoledronic acid was done with subsequent resolution of hypercalcemia. However, this was only temporary given that the underlying disease process driving the production of 1,25-OHD had not been addressed. Various other treatment options were considered including a repeat dose of bisphosphonate, denosumab, ketoconazole and hydroxychloroquine, but since hypercalcemia was only mild, supportive measures were continued. An extensive workup revealed splenomegaly, lymphadenopathy, bilateral renomegaly and bilateral pulmonary ground glass opacities and nodules. Infectious workup and bone marrow biopsy were negative. Although non-specific, an elevated angiotensin converting enzyme (ACE) level (359 units/L; ref: 13-100 units/L) suggested an underlying granulomatous process. Renal biopsy showed non-caseating granulomas. The most likely unifying diagnosis was thought to be sarcoidosis, however presence of hypogammaglobinemia also raised suspicion for a granulomatous form of Common Variable Immunodeficiency (CVID) which, albeit rare, has previously been reported to be associated with hypercalcemia. Patient was started on empiric treatment with steroids and intravenous immunoglobulin following which calcium, 1,25-OHD and ACE levels normalized. Conclusion: Granulomatous form of CVID is a rare entity but should be considered in a patient presenting with 1,25-OHD mediated hypercalcemia and hypogammaglobulinemia. Treatment of this entity during an ongoing diagnostic workup can be challenging, particularly if the use of steroids is contraindicated due to potential interference with diagnostic investigations.